The effect of Ni doping on the properties of ZnO thin films produced by solar pyrolysis spray - ضياء الدين, ونيسي; بالقاسم, حفوضة; جابر, حميداتو (University of El-Oued, 2022)
"The aim of this study is the using of solar energy to elaborate zinc oxide thin films (ZnO) by solar spray pyrolysis technique, then the study of the effect of nickel doping ratio (0, 5, 10, 15 and 20%) on their structural, optical and electric properties. For this purpose, thin films were been deposited on glass substrates heated to temperatures between 375 and 425°C using a solar oven. A study was conducted to examine the properties of these films using X-ray diffraction (structural properties), UV-visible (optical properties) as well as the four probes method (electrical properties). X-ray analysis showed that our samples crystallize according to a hexagonal Wurtzite structure, where the crystals of the prepared films adopt a preferred orientation along the plane direction (002). While the UV visible analysis showed that the transmittance of the films decreases with the increasing of nickel percentage. The calculation generally showed that Urbach energy (Eu) is directly proportional to nickel percentages as this can be explained by the decrease of structural disorder and defects in these layers. In addition, the optical gap (Eg) decreases with the increase of the nickel percentage in the films. The electrical conductivity (σ) of the films - deduced by four probes method - decreases by increasing of nickel percentage to a minimum value of (0.7 .10-5 ohm-1cm-1) for sprayed film with 20% of Ni. " "الهدف من هذه الدراسة هو استخدام الطاقة الشمسية لإنتاج طبقات رقيقة من أكسيد الزنك (ZnO) بتقنية الرش الحراري الشمسي، ثم دراسة تأثير التغير في نسب التخدير بالنيكل (% 20, 15, 10, 5, 0) على خصائصھا البنيوية والبصرية والكهربائية. لھذا الغرض، تم ترسيب طبقات رقيقة على ركائز زجاجية مسخنة الى درجات حرارة تتراوح بين 375 و 425 درجة مئوية باستخدام فرن شمسي. وأجريت دراسة لفحص خصائص هذه الطبقات باستخدام تقنية حيود الأشعة السينية (الخصائص البنيوية) والأشعة فوق البنفسجية والتحليل الطيفي المرئي (الخصائص البصرية) وكذلك طريقة المجسات الأربعة (الخصائص الكهربائية). أظھر التحلیل بالأشعة السینیة أن عیناتنا تتبلور وفق بنیة سداسية حيث تعتمد بلورات الشرائح المحضرة اتجاھًا مفضلاً على طول المستوى (002). بینما أظهر التحليل المرئي للأشعة فوق البنفسجية أن نفاذية الشرائح تنخفض بزیادة النسبة المئوية للنيكل. أظهر الحساب عمومًا أن طاقة Urbach تتناسب طردا مع نسبة النيكل حیث یمكن تفسیر ذلك بانخفاض العشوائیة والعيوب في ھذه الشرائح. بالإضافة إلى ذلك ، تنخفض الفجوة الضوئیة المانعة ( (Egللشرائح مع زیادة نسبة النيكل في الشريحة. تنخفض الموصلیة الكھربائیة(σ) للشرائح - المستخلصة بواسطة تقنیة المصابر الأربعة - بزيادة نسبة النيكل إلى الحد الأدنى لقیمة (0.7 .10-5 اوم-1 سم-1) عند رش الشريحة بنسبة نيكل قدرها 20 %. "
مذكرات ماستر تخصص طاقات متجددة
Keywords: Solar spray pyrolysis ; Thin films ; Zinc oxide (ZnO); doping ratio ; Solar oven ; UV-visible ; Transmittance ; Urbach Energy (Eu) ; optical band gap enegrgy( Eg).; الرش الحراري ؛ الطبقات الرقیقة ؛ أكسید الزنك (ZnO) ؛ نسبة التخدير؛ فرن شمسي ؛ الأشعة فوق البنفسجیة والمرئیة ؛ النفاذیة ؛ طاقة Urbach ؛ الفجوة الضوئیة المانعة .